The relationship between childhood interpersonal and non-interpersonal trauma and autobiographical memory: a systematic review - Borrelli, Giovanni; Lamberti Zanardi, Annachiara; Scognamiglio, Claudia; Cinquegrana, Vincenza; Perrella, Raffaella (Frontiers in Psychology, 2024)
Childhood trauma can have negative effects on several domains of mental functioning, including Autobiographical Memory (AM). Conflicting results emerge in the scientific literature regarding the effects of childhood trauma on AM. In this review, we explored the relationship between the childhood trauma and AM, classifying childhood trauma as interpersonal, non-interpersonal and overall (interpersonal and noninterpersonal). We carried out a systematic literature review, following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA statement). From searching the PubMed, Scopus, and Web of Science databases, we identified 48 studies conducted from 2014 to 2023, which were included when they: (a) were written in English, (b) investigated the relationship between AM and childhood trauma, (c) included a sample of children, adolescents, or adults who had experienced childhood interpersonal and/or non-interpersonal trauma. Of the 48 eligible studies, 29 referred to trauma of an interpersonal nature, 12 to trauma of a non-interpersonal nature, and 7 to overall trauma. Regarding the relationship between childhood trauma and AM, 24 studies found a negative relationship between childhood interpersonal trauma and AM; among the articles on noninterpersonal trauma, 10 studies found no relevant relationship; in the studies on overall trauma, 4 articles found negative relationship between overall trauma and AM. The literature explored in our systematic review supports the prevalence of a negative relationship between interpersonal childhood trauma and AM. This relationship is present regardless of psychiatric disorders (e.g., Depression, Post Traumatic Stress Disorder, and Personality Disorders), and in the presence of the latter, AM results even more fragmented. Future research should use more accurate methodologies in identifying and classifying childhood trauma in order to more precisely determine its effect on AM.